Parents' perception of self-advocacy of children with myositis: an anonymous online survey - Huber Adam M; Bollar Harriet; Jones Olcay Y; Agarwal Shilpi; Mamyrova Gulnara; Katz James D; Rider Lisa G; White Patience H (BMC, 2011)
Abstract Background Children with complex medical issues experience barriers to the transition of care from pediatric to adult providers. We sought to identify these barriers by elucidating the experiences of patients with idiopathic inflammatory muscle disorders. Methods We collected anonymous survey data using an online website. Patients and their families were solicited from the US and Canada through established clinics for children with idiopathic inflammatory muscle diseases as well as with the aid of a nonprofit organization for the benefit of such individuals. The parents of 45 older children/young adults suffering from idiopathic inflammatory muscle diseases were surveyed. As a basis of comparison, we similarly collected data from the parents of 207 younger children with inflammatory muscle diseases. The survey assessed transition of care issues confronting families of children and young adults with chronic juvenile myositis. Results Regardless of age of the patient, respondents were unlikely to have a designated health care provider assigned to aid in transition of care and were unlikely to be aware of a posted policy concerning transition of care at their pediatrician's office. Additionally, regardless of age, patients and their families were unlikely to have a written plan for moving to adult care. Conclusions We identified deficiencies in the health care experiences of families as pertain to knowledge, self-advocacy, policy, and vocational readiness. Moreover, as children with complex medical issues grow up, parents attribute less self-advocacy to their children's level of independence.